ANALISIS SISTEM PENGENDALIAN INTERNAL PENERIMAAN KAS UD. BERKAH PEMATANG SIMALUNGUN - Eva Sriwiyanti; Vitryani Tarigan; Marintan Saragih (Jurakunman (Jurnal Akuntansi dan Manajemen), 2022)
The Purpose of this study was to determine of control system of internal cash receips UD. Berkah Kabupaten Simalungaun. The research data used is qualitative data sourced from obsevations, documents and interviews,, as for the research population, namely and employess of UD. Berkah by using a sample that is the manager as well as the owner and employess of the financial administration section so that the sample used is 2 resource person.Technical data collection using documentation studies and literature studies with cash flow acceptance analysis techniques with flowchard charts and conducting interviews presented in descriptive form.From the result of the analysis through flowchard sharts and interviews of internal controls from sales in cash receipts, where there are 3 parts including cash sales with direct purchases coming to the place of business. Then through a cash transfer that goes directly to the  UD.Berkah account. Then the last is the cash receipts and sales control system with a 1 week round payment system. Procedures for recording receipts, through which all sales proceeds are entered in the recording of sales transactions through invoices, notes or sales receipts so that they know the type of processing and size, as well as for payment by transfer by looking at the patment transfer receipt and adjusted to the nominal entered. From this proof of payment and transaction, a record can be made which is calculated between cash payments and transfer and adjusted to the amount of money received with the results obtained with the results obtained in accordance with the calculated nominal, then from the result of the calculation of cash receipts reported to the business manager.  Keywords : Cash receipts control system